Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1060028018794005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Bleeding Risk With Antidepressants

Abstract: Clinicians must be aware of the risk of bleeding with SRI use, especially for patients taking NSAIDs. Patient education is prudent for those prescribed NSAIDs and SRIs concurrently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 44 publications
0
33
1
3
Order By: Relevance
“…This raises the possibility that addressing target symptoms such as psychosis or agitation related to depression and CBVD might be associated with benefits that outweigh potential risks; however, this clearly requires further investigation. Although mirtazapine has also been associated with a more benign cardiovascular risk profile36 and less blood-thinning effects than SSRIs,37 thus theoretically reducing risk of further haemorrhagic stroke, we found no evidence of a significant association in our cohort. However, antidepressants were not significantly associated with higher risk of stroke recurrence, consistent with a previous study 9.…”
Section: Discussioncontrasting
confidence: 77%
“…This raises the possibility that addressing target symptoms such as psychosis or agitation related to depression and CBVD might be associated with benefits that outweigh potential risks; however, this clearly requires further investigation. Although mirtazapine has also been associated with a more benign cardiovascular risk profile36 and less blood-thinning effects than SSRIs,37 thus theoretically reducing risk of further haemorrhagic stroke, we found no evidence of a significant association in our cohort. However, antidepressants were not significantly associated with higher risk of stroke recurrence, consistent with a previous study 9.…”
Section: Discussioncontrasting
confidence: 77%
“…We did not find evidence of other differences in the hazard of bleeding associated with antidepressant initiation by specific OAC type, sex, or age. Both OAC and certain types of antidepressants are associated with an increased risk of bleeding [23][24][25]. Previous studies have reported the association of antidepressant use with bleeding risk in OAC users.…”
Section: Discussionmentioning
confidence: 99%
“…Both OAC and certain types of antidepressants are associated with an increased risk of bleeding [ 23 25 ]. Previous studies have reported the association of antidepressant use with bleeding risk in OAC users.…”
Section: Discussionmentioning
confidence: 99%
“…A clear reduction in both prescribed doses, mean serum concentration and the proportion of patients with serum concentrations above the recommended reference range was observed for mirtazapine. Mirtazapine is an atypical antidepressant with a considerable sedative effect prominent in low-dose regimens, and, because of its distinctive receptor profile and anticipated lower risk of adverse drug reactions such as hyponatremia and bleeding, mirtazapine is a frequently used comedication with other antidepressants and might also be a preferred antidepressant in patients with considerable comorbidity and polypharmacy [28][29][30][31]. The prominent reduction in the proportion of individuals with serum concentrations above the recommended reference range observed in our study may imply a reduced risk of adverse effects in these patients.…”
Section: Discussionmentioning
confidence: 99%